SYARAT PERLU DAN CUKUP INTEGRAL HENSTOCK-BOCHNER DAN INTEGRAL HENSTOCK-DUNFORD PADA [a,b] - Solikhin, Solikhin; Hariyanto, Susilo; Sumanto, Y.D; Aziz, Abdul (MATEMATIKA, 2017)
In this paper we study Henstock-Bochner and Henstock-Dunford integral on [a,b]. We discuss some properties of the integrable. For every function which Henstock-Bochner integrable then it is Hentsock-Dunford integrable. The contrary is not true. Further more, let for any and collection is Henstock-equi-integrable. We will show that function is Henstock-Bochner integrable on if only if it is Henstock-Dunford integrable on .